Excellence in Agronomy - TRANSFORM work package. Useful resources: data management, analytics & modelling - CGIAR Initiative on Excellence in Agronomy (International Institute of Tropical Agriculture, 2022)
List of resources available through the TRANSFORM Work Package of the Excellence in Agronomy Initiative along with URL to access those resources.